An efficient Discrete Element Lattice Boltzmann model for simulation of particle-fluid, particle-particle interactions. (2nd April 2017) - Zhang, Pei; Galindo-Torres, S.A.; Tang, Hongwu; Jin, Guangqiu; Scheuermann, A.; Li, Ling
Abstract: In this study, an efficient Discrete Element Lattice Boltzmann Model (DE-LBM) is introduced to simulate mechanical behaviours of multiphase systems involving particle-fluid and particle-particle interactions. The LBM is based on the Multiple Relaxation Time (MRT-LBM) formalism for the fluid phase and the Discrete Element Method for particle motions. A novel algorithm is developed for detecting the particle contact base on particle overlapping areas computed directly from the grid-based LBM data. This contact algorithm achieves the same accuracy in determining the particle contact as provided by the Hertz contact model but is far more efficient computationally. The DE-LBM coupling approach is also modified to unify the different schemes developed previously. A modified Verlet List method for updating the solid occupation fraction is proposed to further speed up the simulation. The new model is validated by a series of simulations including the single particle settling and well-known 'Drafting, Kissing and Tumbling' (DKT) phenomenon found in suspensions. The settling of a large number (2500) of particles in a still fluid is also simulated with predicted concentration profiles matching well the analytic solution. These applications demonstrate the potential of the present DE-LBM model as a powerful numerical tool for simulating multiphase particulate systems encountered in many engineering and science disciplines.